On the role of capital gains in Swedish income inequality - Jesper Roine; Daniel Waldenström (Uppsala University, Department of Economics, 2011)
Realized capital gains are typically disregarded in the study of income inequality. We show that in the case of Sweden this severely underestimates the actual increase in inequality and, in particular, top income shares during recent decades. Using micro panel data to average incomes over longer periods and re-rank individuals according to income excluding capital gains, we show that capital gains indeed are a reoccurring addition to rather than a transitory component in top incomes. Doing the same for lower income groups, however, makes virtually no difference. We also try to find the roots of the recent surge in capital gains-driven inequality in Sweden since the 1980s. While there are no evident changes in terms of who earns these gains (high wage earners vs. top capital income earners), the primary driver instead seems to be the drastic asset price increases on the post-1980 deregulated financial markets.
urn:nbn:se:uu:diva-153262
Keywords: D31; 330; Top incomes; Income inequality; Capital gains; Capital income; Sweden; Welfare state; Wertzuwachssteuer; Einkommensverteilung; Börsenkurs; Finanzmarktregulierung; Schweden